2022
DOI: 10.1039/d1fo02749b
|View full text |Cite
|
Sign up to set email alerts
|

A nascent protein labeling strategy disclosed mitochondrial proteomic responses in punicalagin intervened insulin resistance of HepG2 cells

Abstract: Insulin Resistance (IR), as the common pathophysiological basis, is closely related to a variety of metabolic diseases, such as obesity and diabetes. IR is often accompanied with mitochondrial dysfunction which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The labeling method of the nascent proteins is in agreement with the previous report of our laboratory ( 38 ). In briefly, HepG2 cells were treated with or without PA (300 μM) for 24 h, then label with AHA.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The labeling method of the nascent proteins is in agreement with the previous report of our laboratory ( 38 ). In briefly, HepG2 cells were treated with or without PA (300 μM) for 24 h, then label with AHA.…”
Section: Methodssupporting
confidence: 89%
“…We aimed to investigate the effects of PA-stimulated insulin resistance on nascent proteomics changes using an AHA labeling technique commonly used to probe changes in protein translation ( 37 , 38 ). Phosphorylation proteome analysis indicated that protein translation regulation was involved in PA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…After treatment, the cells were washed with 1× PBS; then, JC-1 staining was analyzed via fluorescence microscopy or scanned with a microplate fluorometer (Fluoroskan Ascent, Thermo Fisher Scientific Inc., Waltham, MA, USA) at 488 nm excitation and with 535 and 590 nm emissions to measure the green and red JC-1 fluorescence, respectively. Each well was scanned by measuring the intensity of each of the 25 squares (of 1 mm 2 area) arranged in a 5 × 5 rectangular array [33].…”
Section: Jc-1 Assay For Determining Mitochondrial Membrane Potential ...mentioning
confidence: 99%